Planeación, programación y control de una obra de edificación - Castre Vásquez, Rodolfo Genaro (2006)
This thesis aims to establish the importance and the advantages of making a planning, programming and control of a construction project. This is achieved by planning and scheduling to a real project, where there was no planning or control of the work. Based on this two analyzes, one of what had happened to get hold planning, and another what really happened you do, and comparison making this comparison, along with what developed in the different chapters, is achieved and aim to establish the importance of planning, scheduling and control in a project. In the early chapters the theoretical basis that supports the development of this thesis which describes in detail the various methods of Planning Programming and Control of common use and innovative in the construction industry shows, several of which were used to the development of this thesis. As an application to this study the planning, programming and control of a particular educational building executed in the city of Tarapoto is included, which for its construction only he had the plans for the project and an informal estimate based on empirical calculations and tables by contractor labor (foreman) tools cutting edge such as e program 510 for costs and Budgets, Microsoft Project, which has powerful processing applications for planning, programming was used for this application and control building works, also Microsoft Office programs and Windows XP were used, which after processing data offered their respective reports which were used for proper comparisons and interpretations. Finally, based on the above, the conclusions that can be reached after the preparation of this thesis project, and recommendations on the importance of developing a good project management reiterated mentioned, and within this, the advantages of developing a planning, programming and control of building work.